2014
DOI: 10.3892/ijo.2014.2777
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-gated K+ channel blocker quinidine inhibits proliferation and induces apoptosis by regulating expression of microRNAs in human glioma U87-MG cells

Abstract: Abstract. accumulating evidence has proved that potassium channels (K + channels) are involved in regulating cell proliferation, cell cycle progression and apoptosis of tumor cells. However, the precise cellular mechanisms are still unknown. in the present study, we investigated the effect and mechanisms of quinidine, a commonly used voltage-gated K + channel blocker, on cell proliferation and apoptosis of human glioma U87-MG cells. We found that quinidine significantly inhibited the proliferation of u87-Mg ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 36 publications
1
29
0
1
Order By: Relevance
“… Mancilla and Rojas, ; 2 Wu, ; 3 Edwards and Weston, ; 4 Rogawski and Barker, ; 5 Caballero et al, ; 6 Mergenthaler et al, ; 7 Ru et al, ; 8 Levite et al, ; 9 Hille, ; 10 Bruner et al, ; 11 Päsler et al, ; 12 Zünkler, ; 13 Duan et al, ; 14 Li et al, ; 15 Liu et al, ; 16 Tarr et al, .…”
Section: Methodsunclassified
“… Mancilla and Rojas, ; 2 Wu, ; 3 Edwards and Weston, ; 4 Rogawski and Barker, ; 5 Caballero et al, ; 6 Mergenthaler et al, ; 7 Ru et al, ; 8 Levite et al, ; 9 Hille, ; 10 Bruner et al, ; 11 Päsler et al, ; 12 Zünkler, ; 13 Duan et al, ; 14 Li et al, ; 15 Liu et al, ; 16 Tarr et al, .…”
Section: Methodsunclassified
“…Furthermore, miR-149-3p was found upregulated in U87-MG cells following treatment of quinidine, a voltage-gated K + channel blocker, leading to proliferation inhibition and apoptosis induction of glioma cells. 22 …”
Section: Mir-149 In Cancer Proliferation and Apoptosismentioning
confidence: 99%
“… 64 Proliferation inhibition and apoptosis induction were observed using expression enhancement of miR-149-3p in glioma cells. 22 Moreover, among various cancers, metastasis was repressed using transfecting miR-149-5p mimics in vitro and in vivo . [29, 35, 36] And chemoresistance to 5-Fluorouracil was suppressed by introducing miR-149-5p mimics in colorectal cancer cells.…”
Section: Mir-149 As Potential Therapeutic Targetsmentioning
confidence: 99%
“…Some microRNAs have been seen to play a role in the formation of cancer and development mechanism. Quinidine is known to have anti-proliferative and pro-apoptotic effects, and Ru et al demonstrated that voltage-gated potassium channel blocker quinidine regulates some miRNAs expression (42). Meng et al (2012) previously reported that IC50 values were reduced in cells treated with miR-155 inhibitor together with taxol compared to a control group treated with taxol alone.…”
Section: Discussionmentioning
confidence: 99%